Efficacy of Cognitive Rehabilitation Therapy on Poststroke Depression among Survivors of First Stroke Attack in Ibadan, Nigeria - Olugbemi Olukolade; Helen O. Osinowo (Behavioural Neurology)
Background and Purpose. Poststroke depression (PSD) is a common complication after stroke. There is no adequate treatment for PSD. This study examined efficacy of cognitive rehabilitation therapy (CRT) in the treatment of PSD among stroke survivors. Methods. An experimental design, 30 participants with poststroke depression were randomly assigned into 3 groups of cognitive rehabilitation therapy (CRT), psychoeducation (PE), and the control group (CG). CRT consisted of nine sessions with three-phased sessions focusing on activity stimulation, negative thoughts, and people contacts, PE consisted of nine sessions focusing on knowledge on stroke and poststroke depression, and the CG group was on the waiting list. The BDI scale was used for assessing PSD at posttest. Results. There was a significant difference in the efficacy of CRT, PE, and the CG on PSD, with CRT–CG mean difference of −9.4 ± 3.11 and PE–CG 1.0 ± 3.83. Furthermore, stress was not a confounding variable on the efficacy of CRT. The type of therapy significantly influenced PSD at posttest, with the CRT having greater mean reduction to CG (−11.1 ± 3.1) than PE to the CG (3.0 ± 3.8). Conclusions. Cognitive rehabilitation therapy significantly reduced poststroke depression. Hence, it should be integrated as an adjunct treatment of poststroke depression.